(untitled) (Research, Society and Development, 2021)
Objective: To describe the impacts caused on the mental health of nursing professionals in the Covid-19 pandemic. Method: This is an integrative literature review study, focused on the impacts that the pandemic brought to the mental health of nurses. A survey of articles published in the database of Latin American and Caribbean Literature in Health Science, Scientific Electronic Library Online, Nursing Databases and Medical Literature Analysis and Retrievel System Online was carried out. Results: 15 publications were included in the final study sample. Identification of causes and difficulties such as: exposure of professionals to the virus, long working hours, limited resources, patients’ suffering, concern with contaminating family members, psychological pressure for the great responsibility to save lives. Conclusion: The COVID-19 pandemic, the exposure of nursing professionals to excessive working conditions, direct contact with infected patients, brought situations such as illness and insufficient number of professionals to meet the demand. Psychological support for these professionals and better working conditions are of paramount importance in this pandemic context.